«Faire l’Homme» : The Hysterical Subject and the Quest for Femininity in Antonioni’s "Deserto rosso" (Comparatismi, 2022)
This article sets out to examine Deserto rosso as the site where the main female character can be said to destabilize the female identity quest that characterizes Antonioni’s films of the tetralogy. I shall pursue a Lacanian reflection on the film, only to discuss how the hysteric responds to an identity she perceives as elusive either through the symptom, clearly aimed at an addressee, or through a series of virile identifications aiming to fill a lack of knowledge that she feels as her own. In this sense, Giuliana’s gaze turns out to be dependent on that of the men to whom she relates, in a very peculiar manner. Giuliana, as a hysterical character, may be said to be working from within the cinematic aesthetic of the free indirect style only to disrupt it.
Keywords: Michelangelo Antonioni; Jacques Lacan; Deserto rosso; Giuliana; Free indirect point-of-view shot.